2020
DOI: 10.21203/rs.3.rs-65310/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mediation role of religiosity and hope for the effect of self-stigma on psychological well-being among Virus Corona (COVID-19) patients

Abstract: Background: Over the past few months, there is a significant increase in mortality and morbidity due to Coronavirus disease (Kar, Yasir Arafat, Kabir, Sharma, & Saxena, 2020). Less attention has been paid by researchers to the COVID-19 pandemic, stigmatism, psychological well-being, hope and religiosity and, and how these may impact on the patient's recovery.Method: A random sample consisted of 426 COVID-19 patients, who have resided in the Kingdom of Saudi Arabia, they answered an online questionnaire con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This result differed from one study of North India, which found the highest stigma among the 46 to 60 years age group, while other studies reported no significant association of stigma with age. 15,32,33 But a study conducted among the general population had found more stigma among the younger persons. 34 Patients belonging to the below poverty line category had significantly higher worry about rejoining society after the isolation period than the above poverty line group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result differed from one study of North India, which found the highest stigma among the 46 to 60 years age group, while other studies reported no significant association of stigma with age. 15,32,33 But a study conducted among the general population had found more stigma among the younger persons. 34 Patients belonging to the below poverty line category had significantly higher worry about rejoining society after the isolation period than the above poverty line group.…”
Section: Discussionmentioning
confidence: 99%
“…This result differed from one study of North India, which found the highest stigma among the 46 to 60 years age group, while other studies reported no significant association of stigma with age. 15 , 32 , 33 But a study conducted among the general population had found more stigma among the younger persons. 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most of them use avoidance coping including behavioral disengagement, for example, by giving up trying to deal with illness or giving up attempting to cope, self-blame by criticizing themselves and blaming themselves for things that happen, denial by refusing to believe that it has happened, and distraction, for example, by doing something to think about it less (Adiukwu et al, 2020). The result of the self-stigmatization is that it disrupts the patients' understanding of reality, distorts their way of thinking, and leads to incompetence in carrying out the family and social roles (Al Eid et al, 2021; Zolnikov & Furio, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Coronavirus disease is a pandemic in the globe that was first identified in Wuhan in China in December 2019 (Aungsuroch et al, 2020; Li, Twersky et al, 2020). This respiratory tract infection disease, affecting 210 countries around the world, had not been previously identified in humans (Al Eid et al, 2021; Duy et al, 2020). The disease rapidly spread through the globe, affecting millions of people, and millions died across nearly 210 countries (Abdelhafiz & Alorabi, 2020; World Health Organization [WHO], 2020).…”
mentioning
confidence: 94%